Pengaruh Profitabilitas, Risiko Finansial dan Harga Saham Terhadap Nilai Perusahaan Bank Syariah Indonesia (BSI) Di BEI Periode Tahun 2014 - 2021 - Hartini, Hartini; Marhandrie, Dessy (Jurnal Ilmiah Ekotrans & Erudisi, 2022)
ROA (Return On Assets) having for positive signifikan to assess firm. This matter that if ROA ascends therefore followed by its rise assesses firm. DER (Debt to Equity Ratio) having for positive and signifikan to assess firm. This matter if DER ascends therefore firm point will come on rise. Positive influential stock price and signifikan to assess firm. This matter if stock price ascends therefore firm point will come on rise. ROA, DER and ala stock price simultan (jointly) having for positive and signifikan to assess firm. For investor: one that wants to get investment on Syariah's Bank stock Indonesian to notice fundamental factor as DER and basal ROA judgment gets investment on sectorallies it, since in height DER can make firm point also increases. So even with ROA, in height ROA therefore firm point also tall. For firm: that more notices, keep and increases DER and ROA, since DER and ROA has influence that signifikan to assess firm. So corporate point thus gets increasingly.